PROSEDUR ATAS PENCATATAN UTANG USAHA BERBASIS ENTERPRISE RESOURCE PLANNING PADA PT. DINAMIKA ENERGY INDONESIA - Erina Anggita, (2023)
The accounting information system applied to PT. Dinamika Energy Indonesia is an ERP system that can integrate all business activities within the company. The purpose of this final report is to understand and know more deeply about the existing procedures within the company, especially the procedure for the recording account payable. This final report discusses the process of recording trading debt with an ERP system, in which business debt arises from transaction activities carried out by the other party and must be paid on time. The procedure begins with the use of the services for the operational needs of the company, and then appears the invoice documents for the services from the supplier, which will be sent to the general affairs department. The general affairs department checks and enters the data into the ERP system and makes a voucher that will be sent to the accounting and finance departments. The department of accounting and finance will confirm the results of the input made by public affairs in the ERP system and then make the payment and record it in the supplier payment menu system. One of the data and information used is the result of observations carried out during the three-month fieldwork practice, which is then processed using qualitative descriptive analysis methods. The result obtained from this writing is to gain knowledge about ERP-based accounts payable recording procedures.